Consumer reference (of red-fleshed apples) an quantification of quality related traits, particularly skin and flesh colour, in apple breeding families - Thovhogi, Fhatuwani (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScAgric (Horticulture))--University of Stellenbosch, 2009.